2023
DOI: 10.6026/97320630019133
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich fibrin and titanium-prepared platelet-rich fibrin in endoperio lesion management

Abstract: Endo-perio lesions involve a variety of therapy choices that will lead to the best possible elimination of infection. Various therapy approaches have been investigated for curing of patients affected by endo-perio abnormalities. One of the second-generation platelet derivatives is plasma enriched with platelet (PRP).They may aid in the healing of wounds. Enhanced with platelets cells and several growth factors, platelet-rich fibrin (PRF) promotes repair and healing and regeneration of tissue at the periapical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Another systemic review by Ardila and Vivares‐Builes (Ardila & Vivares‐Builes, 2022 ) found that most studies treated EPLs with simultaneous endodontic and periodontal treatment, with a majority resulting in a statistically significant improvement in probing depths. Recent studies have focused on modern treatment advancements such as guided bone regeneration and incorporating platelet‐rich fibrin, which have both exhibited success in periodontal healing and attachment gain (AlJasser et al, 2021 ; Makkad, 2023 ). A systematic review by Oktawati et al ( 2020 ) found that traditional root canal treatment in conjunction with bone grafting was the most common treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…Another systemic review by Ardila and Vivares‐Builes (Ardila & Vivares‐Builes, 2022 ) found that most studies treated EPLs with simultaneous endodontic and periodontal treatment, with a majority resulting in a statistically significant improvement in probing depths. Recent studies have focused on modern treatment advancements such as guided bone regeneration and incorporating platelet‐rich fibrin, which have both exhibited success in periodontal healing and attachment gain (AlJasser et al, 2021 ; Makkad, 2023 ). A systematic review by Oktawati et al ( 2020 ) found that traditional root canal treatment in conjunction with bone grafting was the most common treatment modality.…”
Section: Introductionmentioning
confidence: 99%